THE IMPACT OF PERCEIVED RISKS TOWARD PURCHASE INVENTION OF PRIVATE LABEL BRANDS (PLBs) IN FOOD AND GROCERIES CATEGORY / SIONG WEI TENG - SIONG, WEI TENG (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Over the years, private label brands (PLBs) are considered as a cheaper brand that associated with the low quality image by Malaysian. This led to perceived risk occurs and discourage them to purchase. Nevertheless, most of the businesses or retailers do not aware of this fact. This study aims to insight the perceived risk dimensions and the impact on consumers' purchase intention toward private label food and groceries. Which risk is the most influential to the purchase intention? Pearson correlation and multiple linear regression analysis are used to investigate the relationship. The result shows that financial risk, social risk, physical risk and performance risk had a significant relationship toward purchase i~tention of PLBs. Interestingly, performance risk was found to be the most influential. This study will be valuable and meaningful to study customer perspective toward private label brands which are applicable in the improvement of branding management or marketing strategies.